2019
DOI: 10.1177/1934578x19858223
|View full text |Cite
|
Sign up to set email alerts
|

Sense Ginsenosides From Ginsengs: Structure-Activity Relationship in Autophagy

Abstract: The term ginseng refers to the dried roots of several plants belonging to the genus Panax of the Araliaceae family. The 3 major commercial ginsengs are Panax notoginseng (Burk.) F.H. Chen (Notoginseng), P. ginseng C.A. Meyer (Ginseng), and P. quinquefolius L. (American ginseng), which have been used as herbal medicines. Over 18,000 papers on ginsengs have been published on the basis of their structural diversity and biological activities. Many reviews have summarized the phytochemistry, pharmacology, and clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…A variety of active ingredients in Gujiansan can regulate the expression of autophagy-related proteins to regulate the process of autophagy. Ginsenosides from ginseng (including American ginseng and Tian Qi) can regulate autophagic activity [ 32 ]. G. lucidum triterpene extract (GLT) induces the formation of autophagic vacuoles and upregulates the protein expression of Beclin-1 and LC-3 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A variety of active ingredients in Gujiansan can regulate the expression of autophagy-related proteins to regulate the process of autophagy. Ginsenosides from ginseng (including American ginseng and Tian Qi) can regulate autophagic activity [ 32 ]. G. lucidum triterpene extract (GLT) induces the formation of autophagic vacuoles and upregulates the protein expression of Beclin-1 and LC-3 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of chemical structure, both PPD and PPT types contain hydroxyl groups at C-3, C-12, and C-20 positions, but PPD has one less hydroxyl group at position 6 than PPT. Furthermore, sugar units are linked to them in different positions such that PPD is either at C-3 or C-20, but PPT is either at C-6 or C-20 ( Wu et al, 2019b ). It is known that Panax ginseng processing involves oxidation, hydrolysis, and/or dehydration, which can produce a series of artificial compounds that are biologically active.…”
Section: Triterpenesmentioning
confidence: 99%
“…In a SAR study, different saponin chemical backbones have been shown to affect autophagy, which plays a role in neurodegenerative disease pathogenesis. Saponins of the PPT type inhibit autophagy, while saponins of the PPD type and their transformed types promote autophagy ( Wu et al, 2019b ). Stereoisomers significantly influence PNS’s pharmacological activity in particular.…”
Section: Triterpenesmentioning
confidence: 99%
“…They are extensively used for diverse beneficial effects on myocardial infarction, stroke, and ischemia/reperfusion injury [ [20] , [21] , [22] ]. Currently, about 250 ginsenosides have been isolated and identified, which are mainly divided into three groups, protopanaxadiol (PPD, such as Rb1, Rb2, Rc, Rd, Rg3), protopanaxatriol (PPT, such as Re, Rf, Rg1, Rh1), and oleanolic acid (OA, such as Ro) [ 23 ]. Proteomic analysis has shown that total ginsenosides (GS) can increase the expression of proteins in the TCA cycle to enhance cardiac energy metabolism in the ischemic rat [ 24 ].…”
Section: Introductionmentioning
confidence: 99%